Evaluation of 100 cases of ascites - Mahmood, Ghulam; Debnath, CR; Mandal, AK (Mymensingh Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Mymensingh Med J. 2009 Jan;18(1):62-66. The abstract of this article is available on the PubMed website